Glucose release kinetics of different feed ingredients and their impact on short-term growth of pigs by influencing carbon-nitrogen supply synchronization - Mingyi Huang; Lei Xue; Yifan Wu; Qinzheng Sun; Yanwei Xu; Jia Li; Xiaoyi Yu; Yu Cao; Jingyi Huang; Zeyu Zhang; Jinbiao Zhao; Dandan Han; et al. (Journal of Animal Science and Biotechnology)
Abstract Background Pigs fed diets with different ingredients but identical nutritional levels show significant differences in growth performance, indicating that growth may also be influenced by the synchronicity of dietary carbon and nitrogen supply. Therefore, this study aimed to determine glucose release kinetics of various feed ingredients, to investigate a glucose release pattern that is conducive to synchronized carbon–nitrogen supply, and to elucidate the underlying mechanisms by which this synchronization optimizes growth of pigs. Results We analyzed the glucose release kinetics of 23 feed ingredients in vitro and found that their glucose release rates and amounts varied greatly. Based on this, a nitrogen-free diet and 5 purified diets, which represented the observed variations in glucose release rates and quantities among feed ingredients, were designed for 18 ileal-cannulated pigs. The results demonstrated that slower glucose release pattern could disrupt the synchrony of dietary carbon and nitrogen supply, reducing the growth of pigs and increasing nitrogen losses. Specifically, the diet with slower and moderate amounts of glucose release showed a relatively slower release of amino acids. Pigs fed this diet had the lower amino acid digestibility and the enrichment of harmful bacteria, such as Streptococcus, in the terminal ileum. Conversely, the diets with slower and lower glucose release exhibited a relatively rapid release of amino acids but also resulted in poor growth. They increased glucogenic amino acid digestibility and potentially enriched bacteria involved in nitrogen cycling and carbon metabolism. Notably, only the diet with rapid glucose release achieved synchronized and rapid release of nutrients. Pigs fed this diet exhibited higher amino acid digestibility, decreased harmful bacteria enrichment, improved nutrient utilization, and enhanced short-term growth performance. Conclusions Our research analyzed significant differences in glucose release kinetics among swine feed ingredients and revealed that slow glucose release disrupted dietary carbon–nitrogen supply synchrony, shifting amino acid utilization and enriching pathogens, negatively impacting growth and nutrient utilization. Consequently, choosing feed ingredients releasing glucose at a rapid rate to balance dietary carbon and nitrogen supply helps promote pig growth, and ensures efficient feed utilization.